Pengaruh Variabel Makroekonomi (SBIS, Inflasi, dan Nilai Tukar) Terhadap Harga Saham Syariah Sektor Properti yang Terdaftar di Jakarta Islamic Index Tahun 2018-2021 - Azizi, M. Riza (Rifa'Institute, 2023)
Understanding market conditions and their impact on equity is crucial for investment decisions. This study examines the influence of macroeconomic variables on the stock prices of shariah-compliant property sector companies listed on the Jakarta Islamic Index (JII) from 2018 to 2021. The variables analyzed include Shariah Bank Indonesia Certificates (SBIS), inflation, and exchange rates.This research explores the impact of these macroeconomic variables on stock prices in the shariah-compliant property sector, providing insights for investors and policymakers to understand stock price determinants. Panel regression analysis using the Random Effect Model equation is conducted. Monthly data from JII-listed property sector stock issuers and relevant macroeconomic variables are collected. Eviews 10 software is used for econometric analysis.The findings indicate that SBIS has a positive influence on stock prices (coefficient = 0.017568, probability = 0.0000), while inflation and exchange rates do not have significant effects.Understanding the influence of macroeconomic variables, particularly SBIS, is crucial for investment decisions in the shariah-compliant property sector. Further research can explore additional variables and time periods for a comprehensive understanding of stock price dynamics. This research explores the impact of these macroeconomic variables on stock prices in the shariah-compliant property sector, providing insights for investors and policymakers to understand stock price determinants. Panel regression analysis using the Random Effect Model equation is conducted. Monthly data from JII-listed property sector stock issuers and relevant macroeconomic variables are collected. Eviews 10 software is used for econometric analysis. The findings indicate that SBIS has a positive influence on stock prices (coefficient = 0.017568, probability = 0.0000), while inflation and exchange rates do not have significant effects. Understanding the influence of macroeconomic variables, particularly SBIS, is crucial for investment decisions in the shariah-compliant property sector. Further research can explore additional variables and time periods for a comprehensive understanding of stock price dynamics.